Pengembangan Bahan Ajar Bahasa Arab yang Kontekstual dan Berbasis Kurikulum di Era Digital - Nurul Atifah Suyuti; Andi Abdul Hamzah (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The digital era brings new challenges and opportunities in Arabic language learning, so the development of innovative and adaptive curriculum-based teaching materials is very important. This article discusses innovations in the development of Arabic language teaching materials that utilize digital technology, such as multimedia, mobile applications, and interactive e-learning platforms, to create a more effective, engaging, and contextual learning experience. With a qualitative approach and case studies in secondary education environments, this study shows that the integration of technology in teaching materials can increase students' interest, motivation, and understanding of Arabic. In addition, this article identifies various obstacles, such as limited infrastructure and teacher readiness, and provides recommendations for sustainable development that is inclusive and responsive to the needs of the times. These findings are expected to be the basis for the development of Arabic language teaching materials that are relevant to the curriculum and able to answer the demands of learning in the digital era.